Cardioprotective effect of Chinese herbal medicine for anthracycline-induced cardiotoxicity in cancer patients: A meta-analysis of prospective studies. Issue 30 (29th July 2022) - Hao, Wei; Shi, You-Yang; Qin, Yue-Nong; Sun, Chen-Ping; Chen, Li-Ying; Wu, Chun-Yu; Bao, Yi-Jia; Liu, Sheng
Abstract : Background: To assess the benefits and harmful effects of Chinese herbal medicine (CHM) formulations in preventing anthracyclines (ANT)-induced cardiotoxicity. Method: The Cochrane Library, Pubmed and EMBASE databases were electronically searched for relevant randomized controlled trials (RCTs) published till December 2021 in English or Chinese-language, in addition to manual searches through the reference lists of the selected papers, and the Chinese Conference Papers Database. Data was extracted by 2 investigators independently. Result: Seventeen RCTs reporting 11 different CHMs were included in this meta-analysis. The use of CHM reduced the occurrence of clinical heart failure (RR 0.48, 95% CI 0.39 to 0.60, P < .01) compared to the control group. Data on subclinical heart failure in terms of LVEF values showed that CHM reduced the occurrence of subclinical heart failure (RR 0.47, 95% CI 0.35 to 0.62, P < .01) as well. Conclusion: CHM is an effective and safe cardioprotective intervention that can potentially prevent ANT-induced cardiotoxicity. However, due to the insufficient quality of the included trials, our results should be interpreted with cautious.